Tanggung Jawab Pelaku Usaha Skincare Atas Tindakan Penjualan Dibawah Harga Pasar - Ode, Anisa; Tjoanda, Merry; Kuahaty, Sarah Selfina (KANJOLI Business Law Review, 2025)
Pricing strategy plays an important role in determining a company's position in the market. One example of an act of selling below market price. Article 20 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, stipulates that "Business actors are prohibited from supplying goods and/or services by selling at a loss or setting very low prices with the intention of eliminating or ensuring the business of their competitors in the relevant market so that it can result in monopolistic practices and/or unfair business competition". One example of a case is an HM influencer and skincare business actor HBC (Hanum Beauty Care), selling products below market price, where this action is detrimental to resellers. This research is normative juridical using a statutory approach and a conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials. The results of the study show that HM has good intentions objectively and uses the principle of responsibility based on the element of error. Based on the act of selling below market price carried out by HM, HM can be held accountable along with payment of compensation when the reseller can prove that the action caused him a loss. Dispute resolution is done through mediation as a non-litigation solution that is more flexible and beneficial to all parties. If no agreement is reached, formal legal channels through KPPU or civil lawsuits can be an alternative to uphold healthy business competition.